Highly Pleomorphic Strains of the Vibrio Predator Pseudoalteromonas piscicida and Their Outer Membrane Vesicles: A Scanning Electron Micrographic Study - Gary P. Richards; Joseph Uknalis; Michael A. Watson (Microorganisms)
Pseudoalteromonas species are recognized for their probiotic roles in reducing pathogens in aquaculture products by secreting a broad range of antimicrobial compounds. Some species, like P. piscicida, are also predators that attack susceptible prey bacteria, including V. parahaemolyticus, by transferring outer membrane vesicles (OMVs) containing digestive compounds to the surface of their prey. These vesicles digest holes in the prey’s cell wall releasing nutrients upon which the Pseudoalteromonas feed. In the present study, scanning electron microscopy was performed on two P. piscicida strains grown in sterile seawater and nutrient-enriched seawater, without the presence of bacterial prey, to determine if the presence of prey or low-nutrient media was required to induce vesicle formation. Micrographs revealed OMV formation and high pleomorphism of P. piscicida in the absence of prey cells and regardless of the nutrient levels of the seawater. Phenotypic characteristics included the presence of (i) vesiculated and non-vesiculated bacteria, (ii) large bulbous OMV versus small OMV, (iii) pilus-like connectors of widely varying lengths to which vesicles were attached, (iv) highly elongated (10 µm long) Pseudoalteromonas cells, and (v) cells that appeared to extend to 50 µm long and to be septating and dividing into short chains and individual cells. The possible contribution of these novel phenotypes to Pseudoalteromonas predation is discussed.